cxcl12a plays an essential role in pharyngeal cartilage development - Wei, Zhaohui; Hong, Qiang; Ding, Zijiao; Liu, Jingwen (Frontiers in Cell and Developmental Biology, 2023)
Background: Neural crest cells constitute a distinct set of multipotent cells that undergo migration along predefined pathways, culmination in the differentiation into a plethora of cell types, including components of the pharyngeal cartilage. The neurocranium is composite structure derived from both cranial neural crest and mesoderm cells, whereas the pharyngeal skeletal elements-including the mandibular and branchial arches-are exclusively formed by craniofacial neural crest cells.Previous studies have elucidated the critical involvement of the chemokine signaling axis Cxcl12b/Cxcr4a in craniofacial development in zebrafish (Danio rerio).Nonetheless, the function contribution of Cxcl12a and Cxcr4b-the homologous counterparts of Cxcl12b and Cxcr4a-remain largely unexplored.In the present study, mutant lines for cxcl12a and cxcr4b were generated employing CRISPR/Cas9 system. Temporal and spatial expression patterns of specific genes were assessed using in situ hybridization and dual-color florescence in situ hybridization techniques. High-resolution confocal microscopy was utilized for in vivo imaging to detect the pharyngeal arch or pouch patterning. Additionally, cartilage formation within the craniofacial region was analyzed via Alcian blue staining, and the proliferation and apoptosis rates of craniofacial neural crest cells were quantified through BrdU incorporation and TUNEL staining.Results: Our data reveals that the deletion of the chemokine gene cxcl12a results in a marked diminution of pharyngeal cartilage elements, attributable to compromised proliferation of post-migratory craniofacial neural crest cells. Subsequent experiments confirmed that Cxcl12a and Cxcl12b exhibit a synergistic influence on pharyngeal arch and pouch formation.Collectively, the present investigation furnishes compelling empirical evidence supporting the indispensable role of Cxcl2a in craniofacial cartilage morphogenesis, albeit cxcr4b mutants exert a minimal impact on this biological process. We delineate that Cxcl12a is essential for chondrogenesis in zebrafish, primarily by promoting the proliferation of craniofacial neural crest cells.Furthermore, we proposed a conceptual framework wherein Cxcl12a and Cxcl12b function synergistically in orchestrating both the pharyngeal arch and pouch morphogenesis.